Seasonal variation of ecosystem photosynthetic capacity and its environmental drivers in global grasslands - Chen, Xiuzhi; Ren, Xiaoli; He, Honglin; Zhang, Li; Lv, Yan (Frontiers in Ecology and Evolution, 2023)
Ecosystem maximum photosynthetic rate (Amax) is an important ecosystem functional property, as it is critical for ecosystem productivity modeling. However, little is known about the mechanisms that regulate the seasonal variations of Amax in grasslands, one of the dominant vegetation types worldwide. In this study, we analyzed the seasonal variations of Amax of grassland sites across the globe and its environmental drivers. First, we found that grassland Amax had strong seasonal variations, mostly showing unimodal curves. Second, the seasonal variation of Amax at all arid grasslands (mean annual vapor pressure deficit (VPD) > 10 hPa) was driven more by changes in canopy physiological property (i.e. maximum photosynthetic rate per leaf area Amaxa) than canopy structural property (i.e. leaf area, presented by LAI), because Amaxa had stronger temporal variability than LAI in these ecosystems. Third, air temperature and VPD drove the seasonal variation of Amax, mainly through its influence on LAI rather than through its influence on Amaxa. Our findings provide new ideas for better parameterizations of Amax in terrestrial ecosystem models.